LAW ENFORCEMENT AND SANCTIONS AGAINST MOTORCYCLE RIDERS WHO DO NOT TURN ON THEIR LIGHTS DURING THE DAY IN SEMARANG CITY BASED ON LAW NUMBER 22 OF 2009 CONCERNING ROAD TRAFFIC AND TRANSPORTATION - Rully Buyung Hardiansyah; Dyah Listyarini; Adi Suliantoro (Universitas Labuhanbatu, 2024)
The safety of motorcyclists on the road is crucial and needs to be prioritized to maintain order and compliance with legal regulations, especially the Traffic Law and Road Transportation Law. Considering this context, the author is interested in selecting a title related to Law Number 22 of 2009 Article 107 concerning traffic and road transportation, focusing on law enforcement and penalties for motorcyclists who do not use headlights during daylight hours in the city of Semarang. This research examines the issues of law enforcement and penalties for motorcyclists who do not turn on their headlights during the day. The methodology employed in this study is qualitative with descriptive analysis. The research findings indicate that traffic officers in the city of Semarang have enforced the law in accordance with the applicable regulations for motorcyclists who do not use headlights. The penalties imposed align with the provisions of Article 107 paragraph 2, which include a maximum imprisonment of 15 days or a fine of up to